Egress from a settlement school: where are the children of Rural Education? - Rosimar Serena Siqueira Esquinsani; Munir José Lauer; Carmem Lúcia Albrecht da Silveira (Universidade Federal do Norte do Tocantins, 2019)
The text - and the research that originated it - starts from an apparently simple question: Where are the children of Rural Education? Where do our pedagogical, political and social efforts go when we devote ourselves to an education in the countryside? Based on the challenging question, the text recomposes information about the departed from the State School of Primary Education October 29, Settlement March 16, in the municipality of Pontão, north of Rio Grande do Sul, in the time cut from 1992 to 2014, totaling 413 subjects surveyed. The text locates the School October 29, emphasizing its four historical periods and presenting data about the graduates, obtained through the Focal Groups procedure, starting from two key categories: schooling and profession. The data point to encouraging prospects: with rare exceptions, family succession on farms is occurring. Young farmers, in their large majority with secondary education, are supporting family farming, with actions for agricultural production and crop diversification, guaranteeing the second generation of farmers in the field. It concludes that the professional and formative success of the children of rural education also represents the success of the project and the pertinence of its existence as a counterpoint and alternative to the dominant schooling model.